Green Pages Philippine agribusiness and food market factbook, 1995-96. (Green Leaf Pub., 1995)
A project of the Institute for Agribusiness Development and Policy of the Center for Research and Communication (CRC), this fact book provides information on the Philippine Agribusiness from "conception" to "consumption". This includes farming, food and non-food processing, marketing and distribution of fresh and processed products, and inputs supply.